Current controllers for optimizing laser cooling on cold atom experiments - Sabulsky, D. O. (Review of scientific instruments, 2024)
The design of a single chip current source based on a common power operational amplifier is presented and demonstrated for the purpose of controlling applied magnetic fields using bias/shim electromagnets in cold atom experiments. The efficacy of the design is realized via application to red-detuned polarization-gradient cooling of 87Rb down to 3 μK. Furthermore, we demonstrate Raman spectroscopy using these devices to apply current and so generate a precise, accurate, and reproducible magnetic field. This work is intended as a short tutorial for new graduate students and postdocs of laser cooling and trapping.